Stakeholders' Perception about Rice Knowledge Management Portal's information - Kumar, Sunil; Sangeetha, V.; Singh, Premlata; Burman, R. Roy; Bhowmik, Arpan (Indian Journal of Extension Education, 2018)
In agriculture various forces are working to change the agricultural extension from a process of technology transfer to a  process of facilitating wide range of communication, information and advocacy services. The midsts of these change  farmers are grappling with the question of how best to harness ICTs to benefit the farming. There was no scale available to  measure farmers' perception towards knowledge portal. Ascale was constructed to measure the perception of the farmers  towards Rice Knowledge Management Portal (RKMP). Likert's summated rating scale technique was followed for  construction of perception scale. Out of 41 statements, 16 statements were retained on the final scale. The validity of the  scale was examined with the help of content validity. Split half method was followed for testing reliability of the scale and  reliability co-efficient of the scale was 0.76 hence, the scale is reliable and can produce consistent results. This scale can be  used to measure farmers' perception beyond the study area with suitable modifications.
Keywords: Item analysis; likert's summated rating; perception scale; reliability; RKMP; rice farmers; validity